Adalimumab therapy reduces hand bone loss in early rheumatoid arthritis: explorative analyses from the PREMIER study. Issue 7 (18th September 2008) - Hoff, M; Kvien, T K; Kälvesten, J; Elden, A; Haugeberg, G
Abstract : Objective: The effect of adalimumab on hand osteoporosis was examined and related to radiographic joint damage in the three treatment arms of the PREMIER study: adalimumab plus methotrexate, adalimumab and methotrexate monotherapy. Predictors of hand bone loss were also searched for. Methods: 768 patients (537 fulfilled 2 years) with rheumatoid arthritis (RA) for less than 3 years, never treated with methotrexate, were included. Hand bone loss was assessed by digital x ray radiogrammetry (DXR) on the same hand radiographs scored with modified Sharp score at baseline, 26, 52 and 104 weeks. For DXR, metacarpal cortical index (MCI) was the primary bone measure. Results: At all time points the rate of percentage DXR–MCI loss was lowest in the combination group (−1.15; −2.16; −3.03) and greatest in the methotrexate monotherapy group (−1.42; −2.87; −4.62), with figures in between for the adalimumab monotherapy group (−1.33; −2.45; −4.03). Significant differences between the combination group and the methotrexate group were seen at 52 (p = 0.009) and 104 weeks (p<0.001). The order of hand bone loss across the three treatment arms was similar to the order of radiographic progression. Older age, elevated C-reactive protein and non-use of adalimumab were predictors of hand bone loss. Conclusion: This study supports a similar pathogenic mechanism for hand bone loss and erosions in RA. The combination of adalimumab and methotrexate seems to arrest hand bone loss less effectively than radiographic joint damage. Quantitative measures of osteoporosis may thus be a more sensitive tool for assessment of inflammatory bone involvement in RA.